Spatial Structure Of Agriculture And Usage Of Eu Funds Relating The Common Agricultural Policy In The Region Of The Middle Pomerania (Research Bulletins of the Faculty of Economic Sciences, 2017)
The article concerns an analysis of spatial structure of agriculture in the region of The Middle Pomerania. The analysis is divided into groups of inner features of agriculture and their holistic approach in the form of general level of agriculture and structural types. Issues of usage of The Common Agricultural Policy (CAP) of UE funds is taken in the consideration in this thesis. Series of agricultural features which distinguish analysed region from other voivodships in Poland are demonstrated, especially the distribution of walnut plantation in the general farmland.
Keywords: agriculture; The Common Agricultural Policy (CAP); The Middle Pomerania; spatial structure; region